MORE THAN MINIMUM CONSCIOUSNESS: APPALLIC SYNDROME - Babanazarov Umid Turobkulovich; Khaitov Dilshod Khayotovich (Journal Park Publishing, 2024)
Apallic syndrome (vegetative state or social brain death), which occurs after acute cerebral hypoxia, is a well-known condition that requires immediate intensive care and coordinated work of medical personnel. In acute brain hypoxia, the cortex is predominantly affected. In the traumatic status of apallic syndrome, a significant contribution to the development of apallic syndrome, in addition to edema of the white matter, is made by compression of the midbrain with the ensuing consequences. Such clinical cases that suddenly arise after acute damage to the cerebral cortex or parts of the brain stem are manifested by various general cerebral symptoms. This article is a review of clinical cases with apallic syndrome.
Keywords: vegetative state, hypoxic encephalopathy, cerebral edema, respiratory instability, pathological reflexes, parenteral nutrition, neuroprotection.